Keterlibatan Pihak Ketiga Dalam Perjanjian Pinjaman Online - Leluly, Hervy Welem; Pesulima, Theresia Louize; Balik, Agustina (Faculty of Law Universitas Pattimura, 2025)
Financial Services Authority Regulation Number 10/POJK.05/2022 concerning Information Technology-Based Joint Funding Services, in Article 44 paragraph (1) letter c states that: